Computation of Differential, Integral Operators and Quantitative Structure–Property Analysis of Boron α-Icosahedral Nanosheet - Khalil Hadi Hakami; Abdul Rauf Khan; Saad Amin Bhatti (Journal of Mathematics)
In its crystalline state, the α-icosahedral nanosheet of boron demonstrates superconductivity and thermal electronic properties. Mathematical research on a graph’s structure yields a graph descriptor, a numerical measure. Chemical graph theory employs connectivity descriptors to analyze molecular structures, providing crucial insights into many chemical compounds’ chemical and biological characteristics. These characteristics benefit physicists, chemists, and medical and pharmaceutical specialists. In this paper, the idea of reverse degree–based RdM-polynomial is initiated, and differential and integral operators are computed. We formulate reverse degree–based topological descriptors based on this concept. In this paper, we examine the boron α-icosahedral nanosheet for this technique. We looked at the physicochemical properties of boron α-icosahedral nanosheets using reverse degree–based topological descriptors and best-fit linear regression models to get an idea of what they are. Researchers are hoping that this strategy will lead them into new areas where they can investigate related studies.